The reproduction of mothering: psychoanalysis and the sociology of gender - Chodorow, Nancy (University of California Press, 1978)
When this best-seller was published, it put the mother-daughter relationship and female psychology on the map. The Reproduction of Mothering was chosen by Contemporary Sociology as one of the ten most influential books of the past twenty-five years. With a new preface by the author, this updated edition is testament to the formative effect that Nancy Chodorow's work continues to exert on psychoanalysis, social science, and the humanities.
Keywords: 1900-1999; amériques; cours; cycles supérieurs; discipline; fem1000; fem9000; figure de la mère; genre; identités LGBTQIA2+; maternité; premier cycle; psychanalyse; périodes historiques; ressource en ligne; régions géographiques; sciences humaines; sociologie; thématiques; états-unis

Capitalisme, Patriarcat et ségrégation professionnelle des sexes - Hartmann, Heidi; Coryell, Rosette (Questions Féministes, 1978)
Keywords: 1600-1699; 1700-1799; 1800-1899; 1900-1999; amérique du nord; amériques; angleterre; approches et analyses; capitalisme; corps; cours; discipline; europe; france; féminisme matérialiste; histoire et politique; patriarcat; premier cycle; périodes historiques; rapports sociaux de sexe; régions géographiques; sciences humaines; soc1016; sociologie; systèmes d'oppressions; thématiques; travail; états-unis